Faktor-Faktor yang Berhubungan dengan Pelaksanaan Mekanisme Pendaftaran Open Member Menuju Universal Health Coverage 100% - Lestari, Suci; Sari Murni, Nani; Dwi Priyatno, Akhmad (Jurnal Kesehatan Saelmakers PERDANA (JKSP), 2024)
community’s health status. The research design is a quantitative analytic survey with a cross sectional approach. The population in this study amounted to 43 people. The sample in this study was the entire total population used as a research sample, totaling 43 open member officers in hospitals, health centers, health offices. The results showed that most of the respondents had a good open member implementation mechanism (97.7%), high knowledge (72.1%), positive attitude (97.7%), good ability (86%), good leadership (93%), availability of infrastructure (74.4%), appropriate compensation (60.5%), and low workload (53.5%). It is hoped that the Prabumulih City Health Office can prepare a Standard Operating Procedure (SOP) specifically for officers of the open member mechanism and create On the Job Training, as well as a special team to carry out the open member mechanism at the Health Service, Hospitals and Community Health Centers so that the main duties and functions are not assigned to one person. related to the relatively high workload of officers.